2022
DOI: 10.18632/aging.204333
|View full text |Cite
|
Sign up to set email alerts
|

SENP3 affects the expression of PYCR1 to promote bladder cancer proliferation and EMT transformation by deSUMOylation of STAT3

Abstract: Abnormal activation of signal transducer and activator of transcription 3 (STAT3) has been found in various types of human cancers, including bladder cancer (BC). In our study, we examined the regulation of STAT3 posttranslational modifications (PTMs) and found that SENP3 is high in bladder cancer. Sentrin/SUMO-specific protease3 (SENP3) and STAT3 were highly expressed in BC tissues when compared with tissue adjacent to carcinoma. SENP3 induced STAT3 protein level and p-STAT3 translocating into nuclear through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…When STAT3 expression increases, it induces YAP signaling to promote lung tumor cell metastasis [ 53 ]. Nuclear translocation of STAT3 has been reported to be critical for the induction of the epithelial–mesenchymal transition (EMT) and increasing metastasis of bladder cancer, and this is mediated via SENP3 as a regulatory factor [ 54 ]. Circ-BGN and circ-RPPH1 are able to stimulate STAT3 signaling to promote gastric and lung tumor cell progression, respectively [ 55 , 56 ].…”
Section: Stat3 Signaling: An Overviewmentioning
confidence: 99%
“…When STAT3 expression increases, it induces YAP signaling to promote lung tumor cell metastasis [ 53 ]. Nuclear translocation of STAT3 has been reported to be critical for the induction of the epithelial–mesenchymal transition (EMT) and increasing metastasis of bladder cancer, and this is mediated via SENP3 as a regulatory factor [ 54 ]. Circ-BGN and circ-RPPH1 are able to stimulate STAT3 signaling to promote gastric and lung tumor cell progression, respectively [ 55 , 56 ].…”
Section: Stat3 Signaling: An Overviewmentioning
confidence: 99%
“…Evidence for the involvement of PYCR1 in cancer mechanisms is growing rapidly. Several studies have implicated PYCR1 in cancer across various cancer types, including colorectal cancer, multiple myeloma, kidney cancer, , liver cancer, prostate cancer, lung cancer, breast cancer, and others. , Many studies have shown that high PYCR1 expression is associated with tumor aggressiveness and poor patient outcomes. , ,,, Furthermore, the knockdown of the PYCR1 gene or the inhibition of PYCR1 enzyme has been shown to inhibit tumorigenesis in multiple cancer cell lines and in vivo animal models. ,,, ,,,,,, Mechanistically, PYCR1 supports cell survival and maintenance in the hypoxic environment of tumor cells when oxygen is not a readily available electron acceptor for NADH. PYCR1 generates NAD + for the TCA cycle in the absence of the electron transport chain, generating proline as a byproduct .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous correlative and mechanistic links of PYCR1 to cancer progression and metastasis have been reported. Many studies have shown that high PYCR1 expression is associated with tumor aggressiveness and poor patient outcomes (Alaqbi et al, 2022; Ding et al, 2017, 2020; Du et al, 2021; Li, Xu, et al, 2022; Li, Liu, et al, 2022; Liu et al, 2021; Oudaert et al, 2022; Shao et al, 2022; Shenoy et al, 2020; Weijin et al, 2019; Xiao et al, 2020; Xu et al, 2021; Zhang et al, 2021), and the knockdown of the PYCR1 gene or the inhibition of PYCR1 enzyme has been shown to inhibit tumorigenesis in cancer cell lines and animal models of cancer (Alaqbi et al, 2022; Cai et al, 2018; Christensen et al, 2020; Ding et al, 2020; Du et al, 2021; Elia et al, 2017; Gao et al, 2020; Li et al, 2023; Li, Liu, et al, 2022; Li, Xu, et al, 2022; Sang et al, 2019; Shenoy et al, 2020; Xiao et al, 2020; Xu et al, 2021; Yan et al, 2019; Zeng et al, 2017; Zhuang et al, 2019). The production of proline via PYCR1 may be an indicator of cancer stem‐like cells, which can survive chemotherapy treatments and lead to relapse in cancer patients (Sharif et al, 2019).…”
Section: Introductionmentioning
confidence: 99%